EXTERNAL ULTRASOUND IN THE DIFFERENTIAL DIAGNOSIS OF ACUTE ABDOMINAL SYNDROME (Proceedings of International Educators Conference, 2023)
Acute abdomen is a medical emergency, in which there is sudden and severe pain in abdomen of recent onset with accompanying signs and symptoms that focus on an abdominal involvement. It can represent a wide spectrum of conditions, ranging from a benign and self-limiting disease to a surgical emergency. Nevertheless, only one quarter of patients who have previously been classified with an acute abdomen actually receive surgical treatment, so the clinical dilemma is if the patients need surgical treatment or not and, furthermore, in which cases the surgical option needs to be urgently adopted. Due to this reason a thorough and logical approach to the diagnosis of abdominal pain is necessary.